2016
DOI: 10.3846/16111699.2015.1137486
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors for Taiwanese Contractors Collaborating With Local Chinese Contractors in Construction Projects

Abstract: Abstract. Regional trade cooperation has become an important component of construction industry due to the Free Trade Agreement. This segment of the market presents many challenges for construction firms. Establishing suitable international partnering relations is an effective strategy for adapting to the additional unpredictability of international markets. This research integrates the Balanced Scorecard system with Fuzzy Analytic Hierarchy Process for comprehensive and quantitative evaluation of the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Wudhikarn (2016) applies BSC-ANP-ZOGP for strategic project selection. Kao et al (2016) apply BSC-FAHP to select construction projects. Yao and Liu (2016) develop a BSC-AHP model for e-government project evaluation.…”
Section: Bsc and Multi-criteria Decision Analysis For Project Selectionmentioning
confidence: 99%
“…Wudhikarn (2016) applies BSC-ANP-ZOGP for strategic project selection. Kao et al (2016) apply BSC-FAHP to select construction projects. Yao and Liu (2016) develop a BSC-AHP model for e-government project evaluation.…”
Section: Bsc and Multi-criteria Decision Analysis For Project Selectionmentioning
confidence: 99%
“…Vafadarnikjoo et al [23] proposed the use of an intuitive fuzzy decision-making trial and evaluation laboratory (DEMATEL) to prioritize the risks associated with construction projects by using the risk breakdown structure (RBS). Kao et al [24] suggested using an integrated fuzzy ANP (analytical network process)-based balanced scorecard system for the evaluation of relevant bilateral factors for the Taiwanese construction sector collaborating with local Chinese contractors. Ahmadi et al [25] analyzed the criteria, prioritized potential risk events, and used the fuzzy AHP technique to quantify them.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [28] made a comparative analysis of AHP and fuzzy AHP to evaluate the potential risk factors at the construction site of a nuclear power plant. Kao et al [57] proposed an integrated fuzzy ANP based balanced scorecard system for evaluation of relevant bilateral factors in Taiwanese construction projects. Burcar Dunovic et al [58] assessed large infrastructure projects by integrating the risk impact cumulative distribution curve based MCDM approach.…”
Section: Previous Studies On Risk Assessment In Construction Projectsmentioning
confidence: 99%